STUDY OF AUTOMOBILE INSURANCE: MAPPING OF A NUCLEUS DEPARTMENT OF REFERENCES IN INDEXED NEWSPAPERS ON THE SCOPUS BASE - Carneiro Escocard, Vitor; de Oliveira Matias, Ítalo; Shimoya, Aldo; de Jesus Aguiar, Cristiane (LINKSCIENCEPLACE, 2026)
This paper is to carry out a bibliometric study of research related to auto insurance indexed to the Scopus database accessed through the CAPES periodical, covering the authors and the countries that publish the most on the subject, the evolution of the surveys over the years, The first and last authors to write about the topic and the most relevant studies in the peak years of publications. In this way it will be possible to create a starting nucleus for future studies in this area. The study initially contemplated 521 articles according to the keywords used where after the filter were selected only 29 articles.